Serum calprotectin in vasculitis associated with antineutrophil cytoplasmic antibodies - E. N. Vorkel; T. M. Reshetnyak; K. S. Nurbaeva; M. V. Cherkasova; G. M. Tarasova; O. N. Egorova; A. M. Lila (Современная ревматология)
Antineutrophil cytoplasmic antibody-associated systemic vasculitis (ANCA-SV) is a group of rare and potentially severe systemic diseases. The search for reliable methods to assess ANCA-SV activity remains relevant. Among the indicators of neutrophil activation that have emerged in clinical practice, the level of serum calprotectin (CLP) stands out, which can be a marker for monitoring vasculitis activity and identifying patients at risk of disease relapse. Objective: to determine serum CLP levels in patients with ANCA-SV. Material and methods. The study group comprised 64 patients (37 with granulomatosis with polyangiitis, 11 with eosinophilic granulomatosis with polyangiitis and 16 with microscopic polyangiitis) aged 18 years and older with a confirmed diagnosis of ANCA-SV. The control group consisted of 30 healthy individuals. ANCA-SV activity was determined using the BVAS index; high activity corresponded to a BVAS value of >3. Damage was assessed using the VDI index. Depending on ANCA-SV activity, patients were divided into two groups: high activity group (group 1, n=33) and low activity group (group 2, n=31). In addition to the generally accepted indicators, serum CLP levels were assessed in all patients with ANCA-SV and healthy donors. Results and discussion. Statistically significant differences (p<0.001) were found in CLP levels in patients with ANCA-SV in groups 1 and 2. A significant correlation was found between CLP concentration and leukocyte count, neutrophil count, neutrophil-to-lymphocyte ratio (NLR) and systemic inflammatory index (SII). Blood CLP levels in ANCA-SV were associated with creatinine levels and not with glomerular filtration rate and urinary sediment. Although CLP concentration depended on disease activity, it did not correlate with acute phase indicators, including ESR and CRP concentration. Conclusion. Serum CLP concentration is significantly higher in patients with active ANCA-SV and is related to NLR and SII inflammatory indices, so we consider the possibility of using this indicator to assess disease activity.